Legal Protection for Child Victims of Sexual Violence in Semarang: Analysis of Decision No. 431/Pid.Sus/2023/PN.Smg - Fikrie, Muhammad Ridho Iksanul; Indah Sri Utari (Law Research Review Quarterly, 2024)
This research seeks to explore the legal safeguards provided to child victims of sexual violence within the Semarang District Court. A qualitative method with a case study was used to analyze primary data from internal court documents. The results show that the Semarang District Court is committed to protecting child victims of sexual violence through existing policies and programs, such as the Child Protection Task Force, special children's courtroom, and rehabilitation programs. Positive impacts of these policies and programs include a sense of security, access to healthcare services, trauma recovery, and stigma prevention. However, this study also found several challenges, such as a lack of human resources and budget, stigma and discrimination against victims, and the sexual objectification of children. Solutions offered to address these challenges include strengthening laws and policies, public education and awareness, and support from various parties. This research indicates that while there has been progress in the legal protection for child victims of sexual violence at the Semarang District Court, there are still areas requiring enhancement to ensure optimal protection for these victims.